Gustav Radbruch's critique of legal positivism - Borowski, Martin (The Cambridge companion to legal positivism, 2021)
Borowski argues that Radbruch’s very important criticism against legal positivism is to be found not in his writings on legal positivism but in his own legal philosophy, especially the so-called Radbruch formula; that the Radbruch formula entails a rejection of the separation thesis on both the level of the criteria for the identification of valid legal norms and the level of the nature of law; and that Radbruch’s explicit claim that legal positivism was to blame for the situation in Germany is unconvincing because the Nazis did not, as a matter of fact, hold that law is law and should be applied according to its plain meaning in all circumstances, but were actually willing to apply a statute contrary to its wording if this suited their purposes.